Graphic organiser as a strategic tool for enhancing summary writing / Shameem Rafik-Galea and Jasvir Kaur Amar Singh - Rafik-Galea, Shameem; Amar Singh, Jasvir Kaur (Universiti Teknologi MARA Cawangan Pahang, 2008)
Summary writing can be used to bridge success in both the English language and content area reading and writing classroom. The ability to summarise a lengthy text or article into its essential ideas is a mark of a proficient reader and writer, thus, making it a critical study skill. Research has shown that summary writing helps improve students' comprehension. Hence, it is considered an effective learning strategy because students must make decisions about the relative importance of elements in a text in order to summarise it and they also need to comprehend a text at a higher level than when they are simply reading it. Students would be able to increase their comprehension of a text if they are well trained in summary writing skills. Summary writing is an essential aspect of the Malaysian upper secondary school curriculum. However, the writers' observations reveal that students are not given adequate practice in summary writing although it is a critical skill. Furthermore, the textbooks in use do not provide appropriate techniques for practice in summary writing. Hence, this paper describes an action research that explores the application of graphic organisers along side other strategies in the teaching of summary writing